2018 IEEE International Conference on Communications (ICC) 2018
DOI: 10.1109/icc.2018.8422819
|View full text |Cite
|
Sign up to set email alerts
|

Outdoor to Indoor Penetration Loss at 28 GHz for Fixed Wireless Access

Abstract: This paper present the results from a 28 GHz channel sounding campaign performed to investigate the effects of outdoor to indoor penetration on the wireless propagation channel characteristics for an urban microcell in a fixed wireless access scenario. The measurements are performed with a realtime channel sounder, which can measure path loss up to 169 dB, and equipped with phased array antennas that allows electrical beam steering for directionally resolved measurements in dynamic environments. Thanks to the … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(17 citation statements)
references
References 21 publications
1
16
0
Order By: Relevance
“…Therefore, with the development of 5G, the design of a cost-optimized FWA network is increasingly placed under scrutiny by both academia and industry [8], [13]. The majority of the investigations carried out focus on enhancing the wireless connectivity of FWA networks [11], [13]. For example, authors in [13] investigated an approach to enhance the link budget in a non-line-of-sight (NLOS) path between a RRH and the CPE of 5G FWA system.…”
Section: G Fwa Network Architectures and Various X-haul Optionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Therefore, with the development of 5G, the design of a cost-optimized FWA network is increasingly placed under scrutiny by both academia and industry [8], [13]. The majority of the investigations carried out focus on enhancing the wireless connectivity of FWA networks [11], [13]. For example, authors in [13] investigated an approach to enhance the link budget in a non-line-of-sight (NLOS) path between a RRH and the CPE of 5G FWA system.…”
Section: G Fwa Network Architectures and Various X-haul Optionsmentioning
confidence: 99%
“…Therefore, there is a need for a cost-effective deployment strategy that is able to satisfy the requirements of both the wireless and the optical transport segments of a FWA network. In the literature there are a number of studies that investigate how to enhance the user experience in optical wireless integrated networks in the context of 5G [9]- [11]. However, the cost-optimal deployment of the wireless and transport segments of a FWA network received minimal attention so far.…”
Section: Introductionmentioning
confidence: 99%
“…More importantly is the outdoor-to-indoor measurements. A 28GHz outdoor-to-indoor measurements made and recorded in [32] [33] were done using a rotating horn antenna channel sounder which can provide an accurate absolute delay information. The result indicated clusters, larger excess delays and larger angular spreads indoor.…”
Section: (V) Penetration Lossmentioning
confidence: 99%
“…For the higher frequency bands of O2I scenarios, studies are found to cover many frequency bands, such as 10, 28, and 60 GHz [6][7][8]. Reference [6] studied the indoor coverage at different frequencies (10, 30, and 60 GHz) in a single building with an outdoor-deployed base station (BS).…”
Section: Current O2i Channel Measurementmentioning
confidence: 99%
“…But the O2I coverage at 60 GHz may be quite difficult for some building types and the throughput was seriously affected, depending on the wall materials, interior layout, and building size. In [7], the authors presented results for path loss, penetration loss for two different type of housing, including single-family unit and multistory brick building.…”
Section: Current O2i Channel Measurementmentioning
confidence: 99%